Hepatic deficiency in transcriptional cofactor TBL1 promotes liver steatosis and hypertriglyceridemia - Kulozik, Philipp; Jones, Allan; Mattijssen, Frits; Rose, Adam J.; Reimann, Anja; Strzoda, Daniela; Kleinsorg, Stefan; Raupp, Christina; Kleinschmidt, Jürgen; Müller-Decker, Karin; Wahli, Walter; Sticht, Carsten; et al. (Cell metabolism, 2011)
The aberrant accumulation of lipids in the liver (“fatty liver”) is tightly associated with several components of the metabolic syndrome, including type 2 diabetes, coronary heart disease, and atherosclerosis. Here we show that the impaired hepatic expression of transcriptional cofactor transducin beta-like (TBL) 1 represents a common feature of mono- and multigenic fatty liver mouse models. Indeed, the liver-specific ablation of TBL1 gene expression in healthy mice promoted hypertriglyceridemia and hepatic steatosis under both normal and high-fat dietary conditions. TBL1 deficiency resulted in inhibition of fatty acid oxidation due to impaired functional cooperation with its heterodimerization partner TBL-related (TBLR) 1 and the nuclear receptor peroxisome proliferator-activated receptor (PPAR) α. As TBL1 expression levels were found to also inversely correlate with liver fat content in human patients, the lack of hepatic TBL1/TBLR1 cofactor activity may represent a molecular rationale for hepatic steatosis in subjects with obesity and the metabolic syndrome.